Instant Granules of Mangosteen Peel (Garcinia Mangostana L.) Ethanol Extract as Antioxidants (Sciences of Pharmacy, 2022)
Free radicals in the air can trigger dangerous diseases, such as cancer and premature aging. To avoid this, antioxidant compounds are needed to donate electrons to free radicals, causing them to become more stable. A powerful antioxidant can be found in nature, including the mangosteen peel. This study aimed to find the best instant granule preparation formula from mangosteen peel extract (MPE) that can be practically consumed and the antioxidant stability during preparation. The wet granulation method was used to make instant granules, which have four formulas with varying amounts of xanthan gum as a suspending agent and maltodextrin as a solubility enhancer. The antioxidant activity was examined using the DPPH method. Based on the findings, formula 4 had the best properties with a drying shrinkage of 1.80%, a flow rate of 11.54 ± 1.56 g/s, repose's angle of 29.112 ± 0.45ᵒ, carr index of 14.043 ± 1.9%, and dispersion rate of 0.164 g/s. There is no residue in the solution. The shape and taste of this formula were most acceptable. The antioxidant activity of the extract and instant granules was not significantly different, with the IC50 of 34.64 μg/ml and 44.12 μg/ml, respectively. Based on the test result, it can be concluded that formula 4 with a concentration of xanthan gum 1% and 20% maltodextrin is a potent antioxidant supplement.